The Interaction of Tradition and Modernity in the Leadership of Papuan Indigenous Peoples: The Case of the Comorian Mimika Tribe, Indonesia - Mokodompit, Limi; Kasnawi, M. Tahir; Abdullah, Suparman; Radjab, Mansyur (International Journal of Qualitative Research, 2024)
This study seeks to ascertain not just the economic repercussions of industrialization on the Mimika tribe in Papua Province, but also how these transformations are altering social and institutional dynamics, notably in terms of traditional leadership. This research was conducted from January 2024 to March 2024 focusing on the Comorian District, especially the Komoro Mimiko Tribe, Papua Province. The data collection techniques used in this study are in-depth interviews with members of the Comoro District, particularly the Comojima tribe, indigenous leaders, industrial workers, and other stakeholders, participatory observation, and holding FGDs with Komoria community groups. The results show that there has been a change in cultural values and traditions stemming from engagement with modern elements. Non-Governmental Organizations (NGOs) prioritizing cultural and ecological diversity advocate for the rights of indigenous communities. Conversely, governmental entities adopt a pragmatic stance, viewing modernization as integral to economic advancement. However, they also acknowledge the significance of preserving cultural sustainability and indigenous rights. To this end, they formulate policies facilitating the harmonization of modernities with traditional practices. The interaction between tradition and modernity sees complexity as well as divergence of views among various stakeholders. In general, these results underscore the difficulties and possibilities associated with striking a balance between modernization and indigenous traditions.